Development of an IPAS E-Module Based on the Contextual Approach for Third-Grade Elementary School Student - Maryati Maryati; Dodik Mulyono; Raden Angga Bagus Kusnanto (CV. Edujavare Publishing, 2026)
The development of Science and Technology (IPTEK) has progressed very rapidly and has a great influence in various fields of life, including in the world of education. This research aimed to develop a contextual approach-based IPAS E-Module for third-grade students at SD Negeri Rejosari that is valid, practical, and effective. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were third-grade students of SD Negeri Rejosari. Data were collected through questionnaires and tests. The product validation results conducted by experts showed that the E-Module obtained a score of 0.94 from the language expert, 0.94 from the media expert, and 0.81 from the material expert, with an average score of 0.90, indicating that the product was categorized as highly valid. The practicality test, conducted through one-to-one trials, teacher assessments, and small-group trials, yielded an average score of 82%, which was categorized as highly practical. The effectiveness test results, based on the comparison of pretest and posttest scores, showed an N-Gain score of 0.71, which falls into the high category. Therefore, the contextual approach-based IPAS E-Module for third-grade students at SD Negeri Rejosari is considered valid, practical, and effective for use in IPAS learning at the elementary school level.